Screening the receptors for Mycoplasma penetrans P35 lipoprotein and characterization of its functional binding domains - Li, Xia; Wang, Xiaoliu; Ye, Youyuan; Zeng, Zhuo; Chen, Li; Peng, Kailan; Xiao, Hua; Gao, Siqi; Luo, Haodang; Zeng, Yanhua (Frontiers in Cellular and Infection Microbiology, 2025)
Mycoplasma penetrans, a prokaryotic microorganism initially isolated from the urine of a patient infected with human immunodeficiency virus (HIV), possesses a distinctive elongated flask-like shape and a tip-like structure. This unique morphology has been shown to facilitate its ability to invade cells both in vitro and in vivo. The adhesion of M. penetrans to host cells relies on lipid-associated membrane proteins (LAMPs), especially P35 lipoprotein, which is exposed on the mycoplasmal surface. In this study, modified Virus Overlay Protein Binding Assay (VOPBA) was employed to identify P35-interacting proteins from membrane protein extracts of SV40-immortalized human uroepithelial (SV-HUC-1) cells. Through recombinant protein binding assays, siRNA-mediated knockdown, ELISA, Far-Western blot, and inhibition experiments, the binding mechanisms and functional domains were further elucidated. Results demonstrated that the P35 lipoprotein interacts with γ-actin (ACTG1). Recombinant P35 specifically bound to both recombinant and endogenous ACTG1 on the host cell membrane. ACTG1 partially inhibited the adhesion of P35 and M. penetrans to host cells. In SV-HUC-1 cells transfected with ACTG1-siRNA, adhesion of P35 and M. penetrans was significantly reduced. Further studies identified the functional domains responsible for binding between P35 and ACTG1 at amino acid residues 35-42 and 179-186. These findings suggest that ACTG1 on the host cell membrane may act as a receptor for the P35 lipoprotein, facilitating the adhesion of M. penetrans to host cells. The identified critical binding regions of P35 represent potential targets for therapeutic interventions against M. penetrans infections.